The right to buy? : selling off public and social housing / Alan Murie. - Murie, Alan (Policy Press, 2016)
In The Right to Buy, Alan Murie provides an authoritative account of the origins, development and impact of the policy across the UK and proposals for its extension in England (and decisions to end it in Scotland and Wales).